ANALYSIS OF LOCAL GOVERNMENT FINANCIAL STATEMENTS (LKPD) IN ORDER TO IMPROVE THE QUALITY OF GOVERNANCE AND THE ACHIEVEMENT OF DEVELOPMENT OUTCOMES IN SOUTH SULAWESI - Tomi Hartanto (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
The performance of regional government administration is a form of illustration of work performance that can be achieved during a certain period. The performance of regional administrations that receive WTP Opinion (Unqualified Opinion) should be better than those that are Non WTP. This study aims to compare the performance of regional government administration in South Sulawesi that received WTP and Non WTP opinions for the 2015-2021 period. The performance of governance between local governments that obtain WTP and Non WTP opinions by using the Economic Growth Rate Product, the Human Development Index (IPM) and the Regional Revenue and Expenditure Budget (APBD). The research implication for local governments is hoped that they can improve the performance of their regional governments, especially in the financial sector by increasing the detection of local revenue sources and being able to manage them properly.